2017
DOI: 10.1016/j.yhbeh.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Sex and estrous cycle differences in immediate early gene activation in the hippocampus and the dorsal striatum after the cue competition task

Abstract: The hippocampus and dorsal striatum are important structures involved in place and response learning strategies respectively. Both sex and estrous cycle phase differences in learning strategy preference exist following cue competition paradigms. Furthermore, significant effects of sex and learning strategy on hippocampal neural plasticity have been reported. However, associations between learning strategy and immediate early gene (IEG) expression in the hippocampus and dorsal striatum are not completely unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 60 publications
1
23
1
Order By: Relevance
“…In contrast, female rats relied more on landmark cues during non-proestrous phases (lower levels of estradiol), and a place strategy during the proestrous phase (higher estradiol levels; [145]). This is consistent with other studies showing that higher levels of estradiol are associated with a place strategy and lower levels of estradiol with response strategies in female rats [63,134,146,147]. These sex differences in the preference of the two learning strategies suggest that males and females may rely on different brain regions during spatial training, and may contribute to sex differences in performance during spatial navigation.…”
Section: Sex Differences In Hippocampus-dependent Cognitionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, female rats relied more on landmark cues during non-proestrous phases (lower levels of estradiol), and a place strategy during the proestrous phase (higher estradiol levels; [145]). This is consistent with other studies showing that higher levels of estradiol are associated with a place strategy and lower levels of estradiol with response strategies in female rats [63,134,146,147]. These sex differences in the preference of the two learning strategies suggest that males and females may rely on different brain regions during spatial training, and may contribute to sex differences in performance during spatial navigation.…”
Section: Sex Differences In Hippocampus-dependent Cognitionsupporting
confidence: 92%
“…4). Yagi et al [147] found that in the CA3 male place learners showed greater cfos expression, while female place learners showed greater zif268 expression. Intriguingly, there were sex by strategy use differences in activation with female place strategy users showing greater zif268 expression but less cfos expression in the CA3 compared to cue strategy users.…”
Section: Sex Differences In Hippocampus-dependent Cognitionmentioning
confidence: 99%
See 3 more Smart Citations